Polymer-based hard carbon negative electrode material, preparation method and application

Preparation of polymer-based hard carbon anode materials by pre-emulsified microsuspension polymerization method solves the problems of low efficiency and low-voltage platform capacity in sodium ion batteries for the first time, achieving efficient sodium ion storage and significantly improved charge and discharge capacity.

CN119735191AActive Publication Date: 2025-04-01CHINA COAL (SHENZHEN) RES INST CO LTD

Patent Information

Application Number
CN202411882180.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-04-01
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

The existing hard carbon anode material has the first low efficiency and low voltage platform capacity in sodium ion batteries, which limits its commercial application.

Method used

The polymer-based hard carbon negative electrode material is prepared by pre-emulsified microsuspension polymerization method, and a rich closed-cell structure is formed using pore-forming agents and free radical initiators to improve the storage capacity of sodium ions.

Benefits of technology

It significantly improves the charge and discharge capacity of sodium ion batteries and the first-time Coulomb efficiency, provides high platform capacity and excellent sodium storage performance, and reduces preparation costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735191A_ABST
    Figure CN119735191A_ABST
Patent Text Reader

Abstract

The invention discloses a polymer-based hard carbon negative electrode material, a preparation method and application, the preparation method comprises the following steps: (1) preparing an aqueous phase solution and an oil phase solution, the aqueous phase solution comprises water, polyvinylpyrrolidone and a cationic surfactant, and the oil phase solution comprises a pore-forming agent, a free radical initiator and a divinyl benzene monomer; (2) uniformly mixing the water-phase solution and the oil-phase solution under an ultrasonic condition to form an emulsion, and (3) transferring the emulsion into a nitrogen atmosphere, heating the emulsion, cooling to room temperature after the reaction is finished, carrying out solid-liquid separation to collect a solid product, washing and drying; and (4) heating the solid product in a nitrogen atmosphere, and carrying out constant-temperature carbonization to obtain the polymer-based hard carbon negative electrode material. Through rich closed pore design, the charge-discharge capacity of the sodium ion battery can be remarkably improved, and the prepared polymer-based hard carbon negative electrode material has potential and can be widely applied to the field of energy storage and energy storage systems such as the sodium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a polymer-based hard carbon negative electrode material, a preparation method and an application thereof. Background Art

[0002] In recent years, lithium-ion batteries have been widely used in society, and sodium ions, as a group element, have attracted extensive attention from researchers due to their abundant resources and similar physical and chemical properties to lithium ions. However, graphite, a common negative electrode material for lithium-ion batteries, is difficult to form a stable intercalation compound with sodium ions due to thermodynamic reasons, so it is difficult for sodium-ion batteries to use graphite as a negative electrode material.

[0003] Researchers have found that hard carbon materials can become the most promising negative electrode materials for sodium ion batteries due to their low discharge platform, high charge and discharge capacity, and excellent cycle stability. Although hard carbon negative electrode materials have many application potentials, their low first coulombic efficiency and low capacity at low voltage platform (<0.1V) limit their commercial application.

[0004] In sodium ion batteries, the charge and discharge curve of hard carbon usually shows a high potential slope region (> 0.1V) and a low potential plateau region (< 0.1V). Although the storage mechanism of sodium is still unclear, a large number of studies have shown that closed pores are the main reason for sodium storage on the low-pressure plateau. To date, many studies have been devoted to increasing the number and size of closed nanopores to maximize the capacity of the resulting hard carbon platform. For example, CN118387859A-A method for preparing a hard carbon negative electrode material with high closed-pore capacity and a sodium ion battery, the method comprises reacting a first carbon source containing polyvalent metal ions with a second carbon source to obtain an aerogel precursor, and then subjecting the aerogel precursor to pyrolysis and steam explosion to obtain a porous pyrolytic carbon material containing polyvalent metal oxides, and then subjecting the porous pyrolytic carbon material to acid washing and heat treatment to finally obtain the high closed-pore capacity hard carbon negative electrode material. However, the above scheme is relatively complicated, and there is still a lack of simple and effective closed-cell construction strategies, which seriously hinders the development of high platform capacity hard carbon negative electrode materials. Therefore, how to develop a low-cost, simple process steps and high platform capacity hard carbon negative electrode material is the problem to be solved by the present invention. Summary of the invention

[0005] In order to solve the above technical problems, the purpose of the present invention is to provide a polymer-based hard carbon negative electrode material, a preparation method and an application. Through a rich closed-pore design, the charge and discharge capacity of the sodium ion battery can be significantly improved. The prepared polymer-based hard carbon negative electrode material has the potential to be widely used in the field of energy storage and energy storage systems such as sodium ion batteries.

[0006] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows:

[0007] In the first aspect of the present invention, the present invention provides a method for preparing a polymer-based hard carbon negative electrode material, as follows:

[0008] (1) preparing an aqueous phase solution and an oil phase solution, wherein the aqueous phase solution comprises water and polyvinyl pyrrolidone and a cationic surfactant dissolved in water, and the oil phase solution comprises an organic solvent and a pore former, a free radical initiator and a divinylbenzene monomer dissolved in the organic solvent;

[0009] (2) mixing the aqueous phase solution and the oil phase solution under ultrasonic conditions to form an emulsion;

[0010] (3) transferring the emulsion to a nitrogen atmosphere, heating the emulsion to 55-95° C., stirring continuously for 4-12 hours, cooling to room temperature after the reaction is completed, collecting the solid product by solid-liquid separation, washing the solid product with ethanol and deionized water, and then drying;

[0011] (4) The solid product is heated in a nitrogen atmosphere to a temperature of 500 to 1700° C. at a rate of 1 to 10° C. / min, and then the solid product is carbonized at a constant temperature for 1 to 8 hours to obtain a polymer-based hard carbon negative electrode material.

[0012] Preferably, in the aqueous phase solution, the mass ratio of water, polyvinyl pyrrolidone and cationic surfactant is (25-75):(0.05-0.1):(0.02-0.04).

[0013] Preferably, in the oil phase solution, the mass ratio of the pore former, the free radical initiator and the divinylbenzene monomer is (30-50):(0.2-0.5):(5-15).

[0014] Preferably, in step (2), the aqueous phase solution is added dropwise to the oil phase solution under ultrasonic conditions to form an emulsion.

[0015] Preferably, in step (1), the cationic surfactant comprises one or more of lauryl ammonium sulfate, hexadecyltrimethylammonium bromide, hexadecyldimethylammonium chloride, benzalkonium bromide and polyethyleneimine.

[0016] Preferably, in step (1), the pore-forming agent includes one or more of polyvinyl alcohol, a mixed solution of toluene and n-heptane, azodicarbonamide, ammonium chloride, and polyvinyl chloride.

[0017] More preferably, the pore-forming agent is a toluene-n-heptane mixed solution formed by mixing toluene and n-heptane in a volume ratio of 2:1.

[0018] Preferably, in step (1), the free radical initiator comprises one or more of cyclohexanone peroxide, azobisisobutyronitrile, ammonium persulfate, dibenzoyl peroxide and azobisisoheptylonitrile.

[0019] In a second aspect of the present invention, the present invention provides a polymer-based hard carbon negative electrode material, which is prepared by the above-mentioned preparation method.

[0020] In the third aspect of the present invention, the present invention proposes an application of a polymer-based hard carbon negative electrode material, and the polymer-based hard carbon negative electrode material prepared above is applied to a sodium ion battery to prepare a negative electrode of the sodium ion battery.

[0021] Beneficial effects:

[0022] The present invention can significantly improve the charge and discharge capacity of the sodium ion battery through a rich closed-cell design, and obtain a higher first coulomb efficiency without any coating or granulation treatment. The polymer-based hard carbon negative electrode material prepared by the present invention has the potential to be widely used in the field of energy storage and energy storage systems such as sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Shown is a SEM image of the sodium ion battery negative electrode material obtained by the present invention.

[0024] Figure 2 Shown is the HRTEM image of the sodium ion battery negative electrode material obtained by the present invention.

[0025] Figure 3 Shown is the first cycle charge and discharge curve of the sodium ion battery negative electrode material obtained by the present invention at a current density of 0.05 A / g.

[0026] Figure 4 Shown are the charge and discharge curves of the sodium ion battery negative electrode material obtained in the present invention from the second cycle to the fifth cycle at a current density of 0.05 A / g.

[0027] Figure 5 Shown are the first cycle charge and discharge curves of various embodiments of the sodium ion battery negative electrode material obtained by the present invention and comparative example 1. DETAILED DESCRIPTION

[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the specific implementation methods of the present invention will be described below with reference to the accompanying drawings. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings and other implementation methods can be obtained based on these drawings without creative work.

[0029] The present invention proposes a method for preparing a polymer-based hard carbon negative electrode material, which uses a pre-emulsified micro-suspension polymerization method to prepare the hard carbon negative electrode material, as follows:

[0030] (1) preparing an aqueous phase solution and an oil phase solution, wherein the aqueous phase solution comprises water, polyvinyl pyrrolidone and a cationic surfactant dissolved in water, and the oil phase solution comprises a pore former, a free radical initiator and a divinylbenzene monomer;

[0031] (2) under ultrasonic conditions, the aqueous phase solution and the oil phase solution are mixed uniformly to form an emulsion. Preferably, the aqueous phase solution is added dropwise to the oil phase solution to form an emulsion.

[0032] (3) transferring the emulsion to a nitrogen atmosphere, heating the emulsion to 55-95° C., stirring continuously for 4-12 hours, cooling to room temperature after the reaction is completed, collecting the solid product by solid-liquid separation, washing the solid product with ethanol and deionized water, and then drying;

[0033] (4) The solid product is heated in a nitrogen atmosphere to a temperature of 500 to 1700° C. at a rate of 1 to 10° C. / min, and then the solid product is carbonized at a constant temperature for 1 to 8 hours to obtain a polymer-based hard carbon negative electrode material.

[0034] In step (1), the cationic surfactant includes one or more of lauryl ammonium sulfate, cetyltrimethylammonium bromide, cetyldimethylammonium chloride, benzalkonium bromide and polyethyleneimine.

[0035] In step (1), the pore-forming agent includes one or more of polyvinyl alcohol, a mixed solution of toluene and n-heptane, azodicarbonamide, ammonium chloride, and polyvinyl chloride. Preferably, the pore-forming agent is a mixed solution of toluene and n-heptane formed by mixing toluene and n-heptane in a volume ratio of 2:1. The toluene n-heptane solution is a good solvent for divinylbenzene monomer, but the polydivinylbenzene chain is insoluble therein. After the polymerization reaction, the extrusion of the toluene n-heptane solution in the polymer is more conducive to forming a porous structure.

[0036] In step (1), the free radical initiator includes one or more of cyclohexanone peroxide, azobisisobutyronitrile, ammonium persulfate, dibenzoyl peroxide and azobisisoheptylnitrile.

[0037] The present invention uses only a pore-forming agent to prepare a polymer-based hard carbon material precursor with abundant pores (i.e., the solid product in step (3)). After subsequent high-temperature carbonization, a rich closed-pore structure can be formed, which provides additional storage sites for sodium ion storage, significantly improving the platform capacity at low potential (<0.1V), and the platform capacity is 244.2mAh / g. The polymer-based hard carbon negative electrode material prepared by the present invention has excellent sodium storage performance. The negative electrode material prepared therefrom is applied to a sodium ion battery, and the first discharge specific capacity is 466.4mAh / g, and the first coulomb efficiency is 73.7%.

[0038] The advantage of the present invention is that the synthesis process of the polymer-based hard carbon negative electrode material does not involve other auxiliary materials such as metals, and has a relatively low overall preparation cost. It also has the advantages of simple operation and high repeatability, which is convenient for large-scale production.

[0039] In summary, the present invention can significantly improve the charge and discharge capacity of sodium ion batteries through this rich closed-cell design, and obtain a higher first coulomb efficiency without any coating or granulation treatment. This negative electrode material has the potential to be widely used in the field of energy storage and energy storage systems such as sodium ion batteries, because it provides a method for synthesizing a polymer-based hard carbon negative electrode material with high charge and discharge capacity and high first coulomb efficiency.

[0040] The technical solution of the present invention is described in detail below with specific embodiments.

[0041] Example 1

[0042] 75 mg of polyvinyl pyrrolidone and 33 mg of hexadecyltrimethylammonium bromide were dissolved in 50 ml of deionized water to prepare an aqueous phase solution.

[0043] 12.5 ml of n-heptane and 25 ml of toluene as pore formers, 0.32 g of azobisisobutyronitrile as a free radical initiator and 10 ml of divinylbenzene monomer were mixed to prepare an oil phase solution.

[0044] Under ultrasonic conditions, the aqueous phase was added dropwise to the oil phase to disperse it evenly to form an emulsion. The emulsion was then transferred to a three-necked flask with nitrogen protection and heated at 75°C for 6 hours. After the reaction was completed, it was cooled to room temperature.

[0045] The cooled product was filtered and the solid product was collected. The collected solid product was repeatedly washed with ethanol and deionized water, respectively. The washed solid product was dried in a vacuum drying oven at 80°C for 12 h. The dried solid product was heated to 1500°C at a heating rate of 5°C / min in a tubular furnace and carbonized at 1500°C for 2 h to obtain a polymer-based hard carbon negative electrode material (HC-1500).

[0046] The polymer-based hard carbon negative electrode material, the conductive agent acetylene black and the binder PVDF were mixed uniformly in a mass ratio of 7:2:1, and N-methylpyrrolidone was added to prepare the negative electrode slurry, which was coated on aluminum foil and dried in a drying oven at 60°C for 12 hours. The above-prepared materials were used as negative electrode sheets, the separator was a polyethylene-polypropylene-polyethylene three-layer film, and the electrolyte was 1M NaPF6 in diethylene glycol dimethyl ether (DIGLYME), and assembled into CR2025 button batteries in a glove box filled with argon (water and oxygen were both <0.1ppm). The charge and discharge test was performed on a Xinwei CT-4008 (Shenzhen Xinwei Electronics Co., Ltd.) with constant current charge and discharge measurements, and the charge and discharge voltage range was 0.01~3V.

[0047] Figure 1 This is a scanning electron microscope photo of the material HC-1500 prepared in the present invention. It can be seen that the prepared material has a lamellar structure.

[0048] Figure 2 This is a high magnification transmission electron microscope image (HRTEM) of the material HC-1500. It can be observed from the figure that HC-1500 has a higher degree of graphitization, which provides more sodium storage sites.

[0049] Figure 3 This is the first cycle charge and discharge curve of the polymer-based hard carbon negative electrode material HC-1500 as a negative electrode material for sodium ion batteries. The charge and discharge voltage range is 0.01-3V, and the current density is 0.05A / g. As can be seen from the figure, its first discharge / charge specific capacity is 466.4 / 343.9mAh / g, and the first coulomb efficiency is 73.7%. The low voltage (<0.1V) platform capacity is 244.2mAh / g.

[0050] Figure 4 The second to fifth cycle charge-discharge curves of the polymer-based hard carbon negative electrode material HC-1500 as a negative electrode material for a sodium ion battery, with a charge-discharge voltage range of 0.01 to 3V and a current density of 0.05A / g. As can be seen from the figure, the GCD curves of the second to fifth cycles can overlap well, indicating that the sodium ion battery negative electrode material HC-1500 has good reversibility.

[0051] Figure 5 The first cycle charge and discharge curves of the embodiment and the comparative examples as the negative electrode material of sodium ion battery, the charge and discharge voltage range is 0.01-3V, and the current density is 0.05A / g. As can be seen from the figure, HC-1500 has a higher low-voltage platform capacity (244.2mAh / g) and the highest first coulombic efficiency (73.7%).

[0052] Example 2

[0053] On the basis of Example 1, other conditions were kept unchanged, and the carbonization temperature in Example 2 was changed to 700° C. for 2 h to obtain a polymer-based hard carbon negative electrode material HC-700.

[0054] The polymer-based hard carbon negative electrode material, the conductive agent acetylene black and the binder PVDF were mixed uniformly in a mass ratio of 7:2:1, and N-methylpyrrolidone was added to prepare the negative electrode slurry, which was coated on aluminum foil and dried in a drying oven at 60°C for 12 hours. The above-prepared materials were used as negative electrode sheets, the separator was a polyethylene-polypropylene-polyethylene three-layer film, and the electrolyte was 1M NaPF6 in diethylene glycol dimethyl ether (DIGLYME), and assembled into CR2025 button batteries in a glove box filled with argon (water and oxygen were both <0.1ppm). The charge and discharge test was performed on a Xinwei CT-4008 (Shenzhen Xinwei Electronics Co., Ltd.) with constant current charge and discharge measurements, and the charge and discharge voltage range was 0.01~3V.

[0055] The measured discharge / charge specific capacities of the polymer-based hard carbon negative electrode material HC-700 at a current density of 0.05A / g in the first cycle were 446.2 / 245.7mAh / g, the first coulombic efficiency was 55.1%, and the low voltage (<0.1V) platform capacity was 96.1mAh / g.

[0056] Example 3

[0057] On the basis of Example 1, other conditions were kept unchanged, and the carbonization temperature in Example 3 was changed to 900° C. for 2 h to obtain a polymer-based hard carbon negative electrode material HC-900.

[0058] The polymer-based hard carbon negative electrode material, the conductive agent acetylene black and the binder PVDF were mixed uniformly in a mass ratio of 7:2:1, and N-methylpyrrolidone was added to prepare the negative electrode slurry, which was coated on aluminum foil and dried in a drying oven at 60°C for 12 hours. The above-prepared materials were used as negative electrode sheets, the separator was a polyethylene-polypropylene-polyethylene three-layer film, and the electrolyte was 1M NaPF6 in diethylene glycol dimethyl ether (DIGLYME), and assembled into CR2025 button batteries in a glove box filled with argon (water and oxygen were both <0.1ppm). The charge and discharge test was performed on a Xinwei CT-4008 (Shenzhen Xinwei Electronics Co., Ltd.) with constant current charge and discharge measurements, and the charge and discharge voltage range was 0.01~3V.

[0059] The measured discharge / charge specific capacities of the polymer-based hard carbon negative electrode material HC-900 at a current density of 0.05A / g in the first cycle were 440.6 / 274.7mAh / g, the first coulombic efficiency was 62.4%, and the low voltage (<0.1V) platform capacity was 140.0mAh / g.

[0060] Example 4

[0061] On the basis of Example 1, other conditions were kept unchanged, and the carbonization temperature in Example 4 was changed to 1100° C. for 2 h to obtain a polymer-based hard carbon negative electrode material HC-1100.

[0062] The polymer-based hard carbon negative electrode material, the conductive agent acetylene black and the binder PVDF were mixed uniformly in a mass ratio of 7:2:1, and N-methylpyrrolidone was added to prepare the negative electrode slurry, which was coated on aluminum foil and dried in a drying oven at 60°C for 12 hours. The above-prepared materials were used as negative electrode sheets, the separator was a polyethylene-polypropylene-polyethylene three-layer film, and the electrolyte was 1M NaPF6 in diethylene glycol dimethyl ether (DIGLYME), and assembled into CR2025 button batteries in a glove box filled with argon (water and oxygen were both <0.1ppm). The charge and discharge test was performed on a Xinwei CT-4008 (Shenzhen Xinwei Electronics Co., Ltd.) with constant current charge and discharge measurements, and the charge and discharge voltage range was 0.01~3V.

[0063] The measured discharge / charge specific capacities of the hard carbon negative electrode material HC-1100 at a current density of 0.05A / g in the first cycle are 391.8 / 246.1mAh / g, the first coulombic efficiency is 62.8%, and the low voltage (<0.1V) platform capacity is 118.5mAh / g.

[0064] Example 5

[0065] On the basis of Example 1, other conditions were kept unchanged, and the carbonization temperature in Example 5 was changed to 1300° C. for 2 h to obtain a polymer-based hard carbon negative electrode material HC-1300.

[0066] The polymer-based hard carbon negative electrode material, the conductive agent acetylene black and the binder PVDF were mixed uniformly in a mass ratio of 7:2:1, and N-methylpyrrolidone was added to prepare the negative electrode slurry, which was coated on aluminum foil and dried in a drying oven at 60°C for 12 hours. The above-prepared materials were used as negative electrode sheets, the separator was a polyethylene-polypropylene-polyethylene three-layer film, and the electrolyte was 1M NaPF6 in diethylene glycol dimethyl ether (DIGLYME), and assembled into CR2025 button batteries in a glove box filled with argon (water and oxygen were both <0.1ppm). The charge and discharge test was performed on a Xinwei CT-4008 (Shenzhen Xinwei Electronics Co., Ltd.) with constant current charge and discharge measurements, and the charge and discharge voltage range was 0.01~3V.

[0067] The measured discharge / charge specific capacities of the hard carbon negative electrode material HC-1300 at a current density of 0.05A / g in the first cycle are 446.0 / 300.6mAh / g, the first coulombic efficiency is 67.4%, and the low voltage (<0.1V) platform capacity is 190.1mAh / g.

[0068] Example 6

[0069] On the basis of Example 1, other conditions were kept unchanged, the oil phase solution and the water phase solution in Example 6 were directly mixed, and other conditions were kept the same, and carbonized at a temperature of 1500° C. for 2 h to obtain a polymer-based hard carbon negative electrode material HC-1500-1.

[0070] The polymer-based hard carbon negative electrode material, the conductive agent acetylene black and the binder PVDF were mixed uniformly in a mass ratio of 7:2:1, and N-methylpyrrolidone was added to prepare the negative electrode slurry, which was coated on aluminum foil and dried in a drying oven at 60°C for 12 hours. The above-prepared materials were used as negative electrode sheets, the separator was a polyethylene-polypropylene-polyethylene three-layer film, and the electrolyte was 1M NaPF6 in diethylene glycol dimethyl ether (DIGLYME), and assembled into CR2025 button batteries in a glove box filled with argon (water and oxygen were both <0.1ppm). The charge and discharge test was performed on a Xinwei CT-4008 (Shenzhen Xinwei Electronics Co., Ltd.) with constant current charge and discharge measurements, and the charge and discharge voltage range was 0.01~3V.

[0071] The measured discharge / charge specific capacities of the hard carbon negative electrode material HC-1500-1 at a current density of 0.05A / g in the first cycle were 461.3 / 337.8mAh / g, the first coulombic efficiency was 73.2%, and the low voltage (<0.1V) platform capacity was 235.5mAh / g.

[0072] It can be seen that, compared with HC-1500 in Example 1, mixing the oil phase and the water phase solution does not have much effect on the electrochemical data of the HC-1500-1 material.

[0073] Example 7

[0074] On the basis of Example 1, other conditions were kept unchanged, and the carbonization temperature in Example 5 was changed to 1700° C. for 2 h to obtain a polymer-based hard carbon negative electrode material HC-1700.

[0075] The polymer-based hard carbon negative electrode material, the conductive agent acetylene black and the binder PVDF were mixed uniformly in a mass ratio of 7:2:1, and N-methylpyrrolidone was added to prepare the negative electrode slurry, which was coated on aluminum foil and dried in a drying oven at 60°C for 12 hours. The above-prepared materials were used as negative electrode sheets, the separator was a polyethylene-polypropylene-polyethylene three-layer film, and the electrolyte was 1M NaPF6 in diethylene glycol dimethyl ether (DIGLYME), and assembled into CR2025 button batteries in a glove box filled with argon (water and oxygen were both <0.1ppm). The charge and discharge test was performed on a Xinwei CT-4008 (Shenzhen Xinwei Electronics Co., Ltd.) with constant current charge and discharge measurements, and the charge and discharge voltage range was 0.01~3V.

[0076] The measured discharge / charge specific capacities of the hard carbon negative electrode material HC-1700 at a current density of 0.05A / g in the first cycle are 430.3 / 300.2mAh / g, the first coulombic efficiency is 69.7%, and the low voltage (<0.1V) platform capacity is 190.6mAh / g.

[0077] This shows that HC-1700 has less low-pressure capacity than HC-1500 when the carbonization temperature rises to 1700°C, indicating that the number of closed pores is relatively reduced at a temperature of 1700°C. This shows the effect of temperature on closed pores in hard carbon materials.

[0078] The embodiments provided by the present invention are described in detail above. Specific examples are used herein to describe the principles and implementation methods of the present invention, and the description of the above embodiments is only used to help understand the core idea of ​​the present invention. It should be pointed out that for ordinary technicians in this technical field, without departing from the principles of the present invention, the present invention can also be improved and modified in a number of ways, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a polymer-based hard carbon negative electrode material, characterized in that: include: (1) preparing an aqueous phase solution and an oil phase solution, wherein the aqueous phase solution comprises water, polyvinyl pyrrolidone and a cationic surfactant dissolved in water, and the oil phase solution comprises a pore former, a free radical initiator and a divinylbenzene monomer; (2) mixing the aqueous phase solution and the oil phase solution under ultrasonic conditions to form an emulsion; (3) transferring the emulsion to a nitrogen atmosphere, heating the emulsion to 55-95° C., stirring continuously for 4-12 hours, cooling to room temperature after the reaction is completed, collecting the solid product by solid-liquid separation, washing the solid product with ethanol and deionized water, and then drying; (4) The solid product is heated in a nitrogen atmosphere to a temperature of 500 to 1700° C. at a rate of 1 to 10° C. / min, and then the solid product is carbonized at a constant temperature for 1 to 8 hours to obtain a polymer-based hard carbon negative electrode material.

2. The preparation method according to claim 1, characterized in that: In the aqueous phase solution, the mass ratio of water, polyvinyl pyrrolidone and cationic surfactant is (25-75):(0.05-0.1):(0.02-0.04).

3. The preparation method according to claim 1, characterized in that: In the oil phase solution, the mass ratio of the pore former, the free radical initiator and the divinylbenzene monomer is (30-50):(0.2-0.5):(5-15).

4. The preparation method according to claim 1, characterized in that: In step (2), the aqueous phase solution is added dropwise to the oil phase solution under ultrasonic conditions to form an emulsion.

5. The preparation method according to claim 1, characterized in that: In step (1), the cationic surfactant includes one or more of lauryl ammonium sulfate, cetyltrimethylammonium bromide, cetyldimethylammonium chloride, benzalkonium bromide and polyethyleneimine.

6. The preparation method according to claim 1, characterized in that: In step (1), the pore-forming agent includes one or more of polyvinyl alcohol, a mixed solution of toluene and n-heptane, azodicarbonamide, ammonium chloride, and polyvinyl chloride.

7. The preparation method according to claim 6, characterized in that: The pore-forming agent is a toluene-n-heptane mixed solution formed by mixing toluene and n-heptane in a volume ratio of 2:

1.

8. The preparation method according to claim 1, characterized in that: In step (1), the free radical initiator includes one or more of cyclohexanone peroxide, azobisisobutyronitrile, ammonium persulfate, dibenzoyl peroxide and azobisisoheptylnitrile.

9. A polymer-based hard carbon negative electrode material, characterized in that: The hard carbon anode material is prepared by the method for preparing the polymer-based hard carbon anode material according to any one of claims 1 to 8.

10. An application of a polymer-based hard carbon negative electrode material, characterized in that: The polymer-based hard carbon negative electrode material prepared by the preparation method according to any one of claims 1 to 8 is applied to a sodium ion battery.

Citation Information

Patent Citations

  • Hard carbon negative electrode material, its preparation method and application

    CN102479942A

  • A preparation method of biomass hard carbon material for negative electrode of sodium ion battery

    CN109004199A

  • Particulate polymeric material

    US20070043147A1

Cited By

  • Hard carbon material coated with conductive polymer coating, preparation method of hard carbon material, negative plate and sodium ion battery

    CN120727803A

  • Nitrogen-oxygen double-doped closed-pore hard carbon nanosphere as well as preparation method and application thereof

    CN121672478A